Potensi Produksi dan Mutu Benih serta Produksi Biomassa Sorghum bicolor Varietas Samurai 2 pada Umur Panen Berbeda sebagai Bahan Pakan: Potency of Seed Quality and Biomass Production of Sorgum bicolor Variety Samurai 2 as Feedstuff on Different Harvest Age - A Najam; L Abdullah; panca dewi manu hara karti; S Hoeman (Jurnal Ilmu Nutrisi dan Teknologi Pakan (Nutrition and Feed Technology Journal), 2021)
Sorghum bicolor var. Samurai 2 can be used as raw material in silage production for ruminant feed. The problem encountered is the difficulty of obtaining certified seeds for commercial sorghum production. So that is necessary to do this research to investigate potential sorghum seed production and its quality of Sorghum bicolor var. Samurai 2. The study was conducted at University Research Station-Jonggol Animal Education and Research Unit, Bogor Agricultural University. The experimental design used was a randomized block design with 4 treatments and 5 replicates. Five individual plants were taken to measure the variables at each treatment set. The treatments consisted of different harvesting times, namely P95 (harvested 95 days after planting), P100, P105 and P110. The variables observed were dry weight of shelled seeds, seed weight per panicle, weight of panicle stalk, panicle weight, seed production per ha, seed moisture content, seed viability test, and shoot biomass production per ha. The results showed that seed production per ha, panicle dry matter weight, fresh seed moisture content, panicle stalk dry weight was not significantly different. Dry weight of shelled seeds, dry weight of seeds per panicle, panicle dry weight, seed viability, weight of biomass per ha were significantly different (p<0.05). The potential for the production of shelled seeds, dry matter of seeds per panicle was the best in the P105 and P110, the viability of the seeds in the P105 and shoot biomass production per ha in the P105. The potential for shelled seed production (4038 kg ha-1), seed dry weight per panicle (54.87 g panicle-1), seed viability (92.8%) and the best biomass production (55.88 tons ha-1) were in treatment P105. Key words: seed production, shoot biomass, Sorghum bicolor, viability